OptiRTC: A physical computing platform for real-time monitoring and control of environmental systems. - Bedig, Alexander. (2017)
Abstract: A physical computing platform, called OptiRTC, is introduced for augmenting the functionality of mechanized infrastructure with real time remote monitoring (RTRM) and control (RTC) capabilities. In contrast to many single-purpose RTRM and RTC systems, the platform leverages off-the-shelf components and a services-oriented architecture (SOA) common to modern enterprise internet applications to achieve degrees of performance, adaptability, scalability, and affordability that make it suitable for a wide range of applications. Funding for the development of OptiRTC was contributed by Geosyntec Consultants as a means of delivering vertically integrated environmental monitoring and control services to facilitate the adaptive and integrated operation of physical and information systems involved in water management, geotechnical and other environmental control applications. An example application of OptiRTC to reduce combined sewer overflow (CSO) discharge volume at Engine House #3 in Washington, D.C. is discussed.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Civil Engineering.; Advisor: Richard Vogel.; Committee: Marcus Quigley, and Alva Couch.; Keywords: Civil engineering, and Computer science.